X-Ray Photoelectron Spectroscopy Stufy in the Anodic Passivity of Sputter-Deposited Nanocrystalline W-Cr Alloys in 12 M HCl - Bhattarai, Jagadish; Hashimoto, Koji (Tribhuvan University Journal, 2011)
Available with full text. Key words: Anodic film; Heumann and stolica; W-Cr Alloys Tribhuvan University Journal Vol XXI, No. 2, 1998 Page: 1-16 Uploaded date: 22 April, 2011